Employment Experiences of Patients with Cancer who Underwent a Permanent Gastrointestinal Stoma —experiences in each period of time from before stoma creation to before and after the resumption of employment - Masujima, Mariko; Tsuruzoe, Hideyuki; Ono, Tomoko (Journal of Japanese Society of Cancer Nursing, 2023)
This study aimed to identify the experiences of patients with cancer with permanent gastrointestinal stomas regarding their employment in each period of time from before stoma creation to after the resumption of employment and examine the nursing support for their employment for each time period.Interviews with 11 subjects were analyzed qualitatively and descriptively to extract the codes, subcategories, and categories for before the stoma creation and before and after resumption of employment.Regarding the work-related experiences of patients with cancer with permanent gastrointestinal stomas, five categories were identified for before stoma creation, which included “judged whether to continue working based on the image and values of the cancer and stoma.” For before resumption of employment, there were seven categories, including “judged whether to resume work based on the current situation,” and “unable to imagine how the cancer treatment and stoma would affect employment and anxiety.” For after the resumption of employment, seven categories were obtained, which included “constant anxiety and tension at work due to concerns regarding fecal leakage and odor.” In addition, the respondents underwent cancer treatment while taking care not to inconvenience those involved at their work during the entire treatment period. Further, they communicated about their cancer and stoma to those involved at work from time to time and received support regarding their resumption of work.Based on these findings, we believe that working patients with cancer with permanent gastrointestinal stomas require support for providing information on their cancer treatment and the impact of the stomas on employment before stoma creation. In addition, support should also be provided for establishing self-care measures for the side effects of their cancer treatment and stoma management at work before resumption, and for reducing anxiety and tension regarding fecal leakage and odor after resumption.